Simon Boccanegra melodramma in un prologo e tre atti - Verdi, Giuseppe (Deutsche Grammophon, 2002)
In this Metropolitan Opera’s 1995 production of Simon Boccanegra director Giancarlo Del Monaco and designer Michael Scott successfully opted for a naturalistic approach. Strictly speaking, much of the décor (the ceiling paintings and furnishings in the Council Chamber scene, for instance) is more reminiscent of the high or even late Renaissance than of the first half of the 14th century, when the real-life Boccanegra flourished. "This Boccanegra seems a model of how the medium video can and ought to be used. It contains no cheap tricks; the balance between broad shots and close-ups is virtually ideal; and the viewer’s attention is focused on specific details, such as Simon’s chalice or Gabriele’s dagger – both in Act II – only when there is good reason for using so attention-grabbing a technique. [www.iclassics.com, Harvey Sachs]